(untitled) (Communications in Computational Physics, 2026)
Simulating gas flow within the divertor, which is a crucial component in nuclear fusion reactors, is essential for assessing and enhancing its design and performance. Traditional methods, such as the direct simulation Monte Carlo and the discrete velocity method, often fall short in efficiency for these simulations. In this study, we utilize the general synthetic iterative scheme to simulate a simplified Tokamak divertor model, demonstrating its fast convergence and asymptotic-preserving properties in complex three-dimensional scenarios. A conservative estimate of speedup by three orders of magnitude is achieved by the general synthetic iterative scheme when compared to the direct simulation Monte Carlo method. We further investigate the relationship between pumping efficiency and factors like temperature, absorptivity, and the Knudsen number, providing valuable insights to guide the design and optimization of divertor structures.